Translanguaging as a Pedagogical Tool in Asia: Roles, Challenges, Opportunities, and Effective Practices - Padchonga, Nelson F.; Cosain, Saleha P.; Calil, Nur Minah A. Hadji; Betwag, April Kris M.; Pelila, John Rey O. (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Educators in Asian classrooms encounter significant challenges in supporting students from linguistically diverse backgrounds. These challenges are rooted in the need to navigate complex layers of language and culture, as well as deeply ingrained communication customs shaped since early childhood. One promising pedagogical approach is translanguaging, which encourages students to draw on their full linguistic repertoire to enhance learning. However, limited research has explored how translanguaging is implemented in real-world classroom settings across Asia. This study conducted a systematic literature review (SLR) of full-text and peer-reviewed publications from 2021 to 2025, sourced from reputable academic databases including ERIC, ScienceDirect, Sage Open, Taylor & Francis, and ProQuest. A total of 36 journal articles were examined for common themes, perceived benefits, and implementation issues associated with translanguaging procedures. The findings show that translanguaging can increase student engagement, improve comprehension, and validate learners’ linguistic identities. However, dominant monolingual ideology, inadequate teacher training, and restrictive institutional regulations impede widespread acceptance. This study finds that translanguaging has a significant potential to promote more inclusive and successful multilingual education in Asian environments. It suggests that teacher education programs and institutional frameworks may incorporate translanguaging into ordinary classroom practice.